Penegakan Hukum Tindak Pidana Kekerasan Seksual Dalam Putusan No.47/Pid.sus/2023/Pn.Gst Berdasarkan Undang Undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual - Maulidina, Mayrani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This paper aims to determine the enforcement of the law on Sexual Violence in Indonesia, using a normative legal research method based on existing legal norms and their application. The purpose of criminal law is to protect human rights. Including in the form of criminal law enforcement, especially Sexual Violence. Sexual violence is any form of sexual activity that is unwanted or has elements of pressure, threats, and coercion. Women are the group most vulnerable to becoming victims. Given the high rate of sexual violence, the Republic of Indonesia has passed Law Number 12 of 2022 concerning Sexual Violence on May 9, 2022, which is applied in a lex-specialis manner which is expected to provide stronger legal protection. As in the decision No.47/Pid.sus/2023/PN.Gst on September 6, 2023, it is explained that the defendant OT, as the Village Head, committed the Crime of Sexual Violence which was carried out continuously, by promising work as staff to the victim witness WT, who is a resident of the village. Based on the defendant's actions, the Panel of Judges charged the defendant OT with an alternative charge in accordance with the provisions of Article 6 letter c of Law Number. 12 of 2022 in conjunction with Article 64 paragraph (1) of the Criminal Code. In this decision, the Panel of Judges also considered preventive and educational aspects in line with the retributive theory and utilitarian theory approaches.